Globalisasi dan Transformasi Institusi Pendidikan Militer di Sekolah Staf dan Komando TNI AL (SESKOAL) - Octavian, Amarulla (Masyarakat: Jurnal Sosiologi, 2014)
Globalization has brought some challenges and threats to the building of national defence and security of many countries, including Indonesia. Many efforts have to be made to answer these challenges and threats. One of these efforts is doing some necessary transformations in the institutions of military education—in this case, The School of Staff and Command of Indonesian Navy (Sekolah Staf dan Komando TNI AL/SESKOAL) that becomes the research subject of this article. This article argues that the attempt of military organization to do adaptation and anticipation in facing globalization can be done by transformation of institution of military education, especially to produce structure or to create new norm about professional military. One of the obstacles for this transformational process is the existing negative stereotype to the SESKOAL, so that that institution had been experiencing marginalization, whereas the institution of military education has significant role in creating professional and competence military. As the consequence, many military personnel hesitate to take part in the institution. The method that used in this research is qualitative method with socio-historical inquiry. This article uses theoretical framework inspired by Anthony Giddens’ thought about structuration.